Numerical Study For The Heat Transfer By Mixed Convection Inside An Enclosure With A Top Wall Sinusoidal Motion - Al-Deen Hussain, Dhia; Jamil Yasin, Nabil; Sleman Abdulla, Ayad (Journal of Engineering and Sustainable Development, 2014)
Heat transfer by mixed convection of air inside an enclosure is investigated numerically. The top wall of the enclosure is assumed to oscillate horizontally with the velocity defined as u = uo sin (ωt). The bottom wall was subjected to a constant heat flux while the other two vertical walls were assumed to be insulted. The basis of the investigation was the two dimensional numerical solutions of the governing equations by using the finite difference method. The effects of Richardson number, Aspect ratio of the enclosure, and lid oscillation speed, on the flow and thermal behavior of the air inside the enclosure were investigated.. The results shows that the fluid flow and energy distributions within the enclosures and heat flux are all enhanced by the decrease in the Richardson number. The results are presented in the form of flow and thermal fields, and a profiles for horizontal components of velocity, temperature , and the local heat flux were also presenteddifference method.